(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Mobile ad-hoc network is the collection of node whichdynamically forms a temporary network without the use ofany existing network infrastructure or centralizedadministration. When the mobility in the network is high andthe topology changes frequently the route maintenanceoverhead in AODV increases. Because nodes can move linkbreakages can occurs. Long path is more vulnerable to linkbreakages and requires high control overhead for itsmaintenance. In this paper we introduce a new modifiedAODV protocol. This new protocol uses stability factor ofintermediate nodes to find the most sable neighbors andtherefore most stable path. This new proposed protocol is SRAODV(Stable Route AODV) protocol. We simulate bothAODV and SR-AODV with ns-2 in similar scenario. We findthat SR-AODV will show better performance than AODV